Context of cancer control in New Zealand. (March 2020) - Sarfati, Diana; Jackson, Christopher
Highlights: NZ faces a rising cancer burden, increasing costs of care, and inequalities in outcomes. NZ has particularly high rates of bowel cancer and melanoma. There are inequalities between Māori and non-Maori in rates of preventable cancers. Cancer survival is improving more slowly in NZ than other comparable countries. There has been a lack of national leadership in cancer planning and policy. Abstract: Cancer is the leading cause of death in New Zealand and the burden of cancer is growing. The number of people who will be diagnosed with cancer will continue to increase and the costs of cancer care are sky-rocketing beyond our capacity to afford it. Cancer outcomes vary depending on where you live and New Zealand's survival rates are falling behind those in comparable countries. New Zealand leads the world in terms of colorectal cancer and melanoma incidence, with prostate, breast, and lung cancers rounding out the top five cancers in terms of incidence. Māori and Pacific people have higher incidence for several preventable cancers, and worse survival than other New Zealanders. New Zealand has a largely publically-funded healthcare system, with the overall responsibility for cancer control planning and policy resting with the Ministry of Health. New Zealand's most recent cancer control strategy was published in 2003, and since then there have been a series of short-term operational plans. Opportunities to strengthen preventive strategies have been missed. This series aims to identify the challenges and opportunities across the cancer control continuum, with lessons that are likely to resonant with many other countries around the world.